2016
DOI: 10.1177/1740349915590006
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of micro or nano cellulose fibers via electroless Ni-P composite coatings

Abstract: NiP composite coatings were prepared on cellulose fiber surface via a simple electroless NiP approach. The metalcoated extent, dispersion extent of micro or nano cellulose fibers and crystalline structure of NiP composite coatings were investigated. The homogeneous hollow composite coatings and metal-coated extent of micro or nano cellulose fibers were improved with the increase in ultrasonic power, and the ideal composite coatings were obtained as ultrasonic up to 960 W. The metallization for cellulose fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These results can also be an evident on the possible agglomeration occured as the CNFs content increased. Reference [23] reported that increasing the volume fraction of CNFs led to weaken the bonding interfaces and promoted stress concentration that was assumably resulted from the porosity and compaction difficulties also agglomeration of CNFs that has a lot of hydroxyl groups. Furthermore, further research is still needed to evaluate the dispersion performance of CNFs particularly when using higher percentage.…”
Section: B Effects Of Cnfs On the 7th Day Compressive Strength And Wmentioning
confidence: 99%
“…These results can also be an evident on the possible agglomeration occured as the CNFs content increased. Reference [23] reported that increasing the volume fraction of CNFs led to weaken the bonding interfaces and promoted stress concentration that was assumably resulted from the porosity and compaction difficulties also agglomeration of CNFs that has a lot of hydroxyl groups. Furthermore, further research is still needed to evaluate the dispersion performance of CNFs particularly when using higher percentage.…”
Section: B Effects Of Cnfs On the 7th Day Compressive Strength And Wmentioning
confidence: 99%
“…It is particularly suitable for forming thin films on an irregularly shaped surface. Electroless plating requires no vacuum system and can be rapidly and easily operated [8][9][10]. The silver mirror reaction (SMR) is one type of electroless plating method.…”
Section: Introductionmentioning
confidence: 99%